PENGENALAN UNIT ALIRAN DAN PENGARUHNYA TERHADAP PENYEBARAN PANAS INJEKSI UAP, RESERVOIR RINCU 1, AREA 4, LAPANGAN MINYAK DURI - Setya Budi, Iwan
Duri Oil Field has been widely known as the world’s largest steamflood project. Eleven areas have been developed including Area 4, object of this study, located in the middle of the field. This area has estimated OOIP of 190 MMBO from Rindu reservoir and 240 MMBO from Pertama/Kedua reservoirs. Challenges remain on reservoir management practice to distribute steam into right place at the right time both vertically and laterally. Reservoir surveillance data show areal distribution sometimes not meeting expectation causing deferred production as heavy oil production strongly correlates with the fluid temperature. There is a need to understand factors controlling steam distribution variation throughout the field. A successful reservoir management requires understanding of reservoir quality variation throughout the field in order to design injection strategy to meet expected production. One of the method often used in reservoir quality assessment is the one proposed by Amaefule, et.al. The strength of this method is that integration geological knowledge and petrophysical properties of reservoir rock. Litho-facies as an expression of structure and texture will be determined from cored wells and is correlated to surrounding wells. The correlation uses sequence stratigraphy principles to ensure reservoir is delineated correctly. Porosity and permeability data then are plotted to see the correlation pattern for each litho-facies. Each litho-facies has a relationship between porosity and permeability and this determines the hydraulic flow characteristics. Porosity represents storage capacity while permeability indicates deliverability of reservoir rock.